Improving Our Understanding of the Death/Life Implicit Association Test. Issue 6 (1st November 2020) - Podlogar, Matthew C.; Gutierrez, Peter M.; Joiner, Thomas E.
Abstract: The "Death/Life" Implicit Association Test (d-IAT) is a reaction-time task which has been associated with past and future suicidal behavior; in some work, the association has been incremental to explicit self-report of suicide risk. Proposed mechanisms for this association relate to one's unwillingness or inability to completely disclose or be introspectively aware of implicit risk. This study investigated moderators of implicit-explicit concordance as well as predictors of d-IAT score unexplained by self-reported suicidal thoughts and behaviors among an online sample of 382 adults with higher demographic suicide risk (i.e., military service members and veterans, men over age 50, and LGBTQ young adults). Before and after controlling for current explicit report, results replicated the finding of a significant relationship between d-IAT score and severity of past suicidal behavior, and additionally indicated that suicide attempt history and wish to live moderated the association between d-IAT score and explicit report. Furthermore, results suggest that poor introspective awareness, rather than deception, may account for differences between implicit and explicit risk assessment. Continuing investigation of moderators and mechanisms of the d-IAT is needed to improve the utility and validity of using implicit suicide risk assessment as a clinical tool.